2021
DOI: 10.1093/mnras/stab060
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric circulation of brown dwarfs and directly imaged exoplanets driven by cloud radiative feedback: effects of rotation

Abstract: Observations of brown dwarfs (BDs), free-floating planetary-mass objects, and directly imaged extrasolar giant planets (EGPs) exhibit rich evidence of large-scale weather. Cloud radiative feedback has been proposed as a potential mechanism driving the vigorous atmospheric circulation on BDs and directly imaged EGPs, and yet it has not been demonstrated in three-dimensional dynamical models at relevant conditions. Here, we present a series of atmospheric circulation models that self-consistently couple dynamics… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 150 publications
(159 reference statements)
4
31
0
Order By: Relevance
“…Tan and Showman (2017) included a parameterization of silicate condensation and latent heating in their GCM study and found that isolated silicate storms can occur when the condensation level sinks below the radiative‐convective boundary due to the onset of moist convection, which could explain the inferred patchiness of clouds and temporal variability of objects at the L‐T transition. Variability is also likely impacted by the rotation rate and cloud radiative feedback (Tan & Showman, 2019, 2020, 2021), such that changes in the Coriolis force with latitude could lead to corresponding changes in cloud opacity and patchiness inline with observations of brown dwarfs at different inclinations, where objects viewed equator‐on are redder and more variable than objects viewed pole‐on (Vos et al., 2017).…”
Section: Insights From Theorymentioning
confidence: 90%
See 1 more Smart Citation
“…Tan and Showman (2017) included a parameterization of silicate condensation and latent heating in their GCM study and found that isolated silicate storms can occur when the condensation level sinks below the radiative‐convective boundary due to the onset of moist convection, which could explain the inferred patchiness of clouds and temporal variability of objects at the L‐T transition. Variability is also likely impacted by the rotation rate and cloud radiative feedback (Tan & Showman, 2019, 2020, 2021), such that changes in the Coriolis force with latitude could lead to corresponding changes in cloud opacity and patchiness inline with observations of brown dwarfs at different inclinations, where objects viewed equator‐on are redder and more variable than objects viewed pole‐on (Vos et al., 2017).…”
Section: Insights From Theorymentioning
confidence: 90%
“…This technique has been useful in revealing how aerosols are transported in an atmosphere, particularly whether they can be lofted to high altitudes to explain muted gas spectral features. Alternatively, parameterized cloud distributions are prescribed onto the 3D grid of the GCM based on observations (M. Roman & Rauscher, 2017) or as 1D columns in which cloud formation is evaluated based on whether condensate vapor is locally supersaturated without advection of the clouds (Harada et al., 2019; Parmentier et al., 2016, 2018, 2021; M. Roman & Rauscher, 2019; M. T. Roman et al., 2020; Tan & Showman, 2017, 2020). More complex 1D cloud models, like DRIFT (Helling et al., 2016, 2019a, 2019b, 2020; G. Lee et al., 2015) and the Ackerman and Marley (2001) model (Lines et al., 2019) have also been incorporated into GCMs in this fashion.…”
Section: Insights From Theorymentioning
confidence: 99%
“…Lee et al 2017;Parmentier et al 2016;Roman & Rauscher 2019). When internal forcing dominates, on the other hand, cloud radiative effects may cause atmospheric variability and turbulence as well as changes in transient waves, as shown by and Tan & Showman (2021) for isolated brown dwarfs for a typical effective temperature anomaly of hundreds of Kelvins.…”
Section: Discussionmentioning
confidence: 95%
“…Measuring the viewing angles of these low-gravity brown dwarfs with maximum amplitudes would allow us to test this possibility, and will be the focus of a future paper. Additionally, using three-dimensional atmospheric circulation models, Tan & Showman (2021) find that the rotation rate likely affects the size of atmospheric features in the atmosphere, and thus alters the variability amplitude driven by these features.…”
Section: The Variability Amplitudes Of Young Brown Dwarfs At 36 Micronmentioning
confidence: 98%